Severe Combined ImmunoDeficient (SCID) mice in biomedical research - TSINGOTJIDOU (Α.Σ. ΤΣΙΓΚΟΤΖΙΔΟΥ), A. S. (Journal of the Hellenic Veterinary Medical Society, 2017)
Mice have been used in cancer research since the last decade of the 19th century. In 1921 inbred strains, that were predisposed to developing tumors, were bred and became available to cancer researchers. The nude mouse, a hairless mutantdiscovered in 1962, is immunodeficient, and thus does not reject tumor transplantations from other species. It lacks a thymus, which is essential for the production of T-cells, lymphocytes that are essential for cellular immunity. In 1983 mice with severecombined immune deficiency (Prkdcscld, commonly referred to as seid) were discovered. Seid mice are even more immunodeficient than nude mice. Tumors from other species are transplanted into seid mice easier. In 1988 two groups of researchers almostsimultaneously succeeded in transplanting elements of the human immune system into seid mice. They had used totally different approaches in creating their human-mouse chimeras. This chimera, named the hu-PBL- seid, was also able to produce humantetanus antibodies when injected with tetanus toxin, further demonstrating that its immune system was functioning as though itwas naturally human. Severe Combined ImmunoDeficient (seid) mice are homozygous for the mutant autosomal recessive gene"seid", which is located at the centromeric end of chromosome 16. Since these mice lack mature, functional lymphocytes, they arehighly susceptible to lethal opportunistic infections. For this reason, they should be maintained in a pathogen free environment. Someseid mice, by an unexplained mechanism, eventually develop minute levels of Β cells and a rudimentary antibody response and are commonly referred to as "leaky". Different genetic manipulations are used to overcome this obstacle. The transfer of the seid mutation onto the Non-Obese Diabetic (NOD), BEIGE (beige mutation results in cytotoxic Τ cell and macrophage defects as well as selective impairment of NK cell functions) and other strains has led to better engraftment of transferred human cells. Lately, mice with targeted mutations have been engineered, including animals with disruption of the recombination activating gene-1(Rag-1) or (Rag-2), β2 microglobulin (B2m) and perforin (PRF1) genes. Any possible combination of the above mentioned mutantshas led to the development of humanized mouse models providing more straightforward assay systems for the study of the human hematolymphoid system. Our personal experience on the use οι seid mice in biomedical research relates to the development of animal models to investigate cancer metastasis in human bone.